COVID-19 triggered a physically active lifestyle of people with cardiovascular diseases: Results of a small Austrian qualitative study - Krczal, Eva; Hyll, Walter (Frontiers in Public Health, 2022)
Objective: This paper explores physical activity patterns and compensation strategies of people with cardiovascular diseases. The aim is to provide insights into the factors and their relationships that may affect physical activity levels positively or negatively during the pandemic. Methods: We adopted a qualitative approach with 35 participants who were purposively sampled from different provinces in Austria, including rural and urban areas. Semi-structured interviews were conducted during the second COVID-19 wave in autumn/winter 2020 and the fourth wave in autumn/winter 2021. Content analysis was applied to explore physical activity patterns, the perceived impact of the pandemic on physical activity as well as strategies adopted by participants to maintain physically active during the pandemic waves. Results: Results show encouraging signs of a recovery or even increase in physical activity during the pandemic waves. The main drivers for maintaining or even increasing physical activity were intrinsic motivation and self-determined motivation relating to the pursue of individual health goals. Furthermore, analysis suggests a reinforcing effect of exercising in green natural areas by decreasing perception of effort and increasing motivation. There was also one group who experienced difficulties in adapting physical activity behaviors. Study participants who were used to exercise indoors struggled to replace accustomed activity patterns with alternatives that were not impacted by lockdown restrictions. Conclusions: This study provides novel qualitative evidence on the effect of COVID-19 lockdowns on physical activity patterns of people with cardiovascular diseases. Public health interventions to enhance a physically active lifestyle during and beyond the Covid-19 pandemic are recommended to target moderate outdoor exercising and enhance adaptive capacities of people with cardiovascular diseases.